The level of interleukin-6, serum calprotectin, and hypersensitive C-reactive protein in Crohn's disease-related mucosal damage: Serum calprotectin, hypersensitive CRP, and interleukin-6 in gut mucosal damage - Zhang, Chuanshuo; Zhou, Fengning; Cao, Xiandong; Qiu, Chenyang; Lu, Mingdian; Yu, Xin; Xiang, Pingping; Yu, Bo; Zhou, Bo (Journal of Medical Biochemistry, 2025)
[Objective] To evaluate calprotectin, hypersensitive C-reactive protein, and interleukin-6 for detecting digestive tract mucosal injury in Crohn's disease (CD) patients.[Methods] 52 patients diagnosed with CD were selected. Fecal samples from the patients were collected to detect calprotectin (ELISA), and serum samples were collected to detect hs-CRP (Immunoturbidimetry) and IL-6 (Chemiluminescence). All patients with CD underwent colonoscopy or capsule endoscopy. According to the modified endoscopic severity index of CD (SES-CD). Comparisons were made between the two groups' variations in calprotectin, hs-CRP, and IL-6 levels, and ROC curves were drawn to analyze the diagnostic efficacy (AUC) of each index and combined detection for mucosal injury.[Results] In the Mucosal injury group, the calprotectin, hs-CRP levels were significantly greater than those in the mucosal healing group. Calprotectin had the highest AUC (0.93, 95% CI: 0.88–0.98), sensitivity (88.5%), and specificity (89.2%) when the critical value was greater than 250μg/g, according to ROC analysis. The AUC of the three indicators' combined detection (logistic regression model) rose to 0.96, which was noticeably superior than that of a single indicator (P
Keywords: Hypersensitive C-reactive protein; Mucosal injury; Interleukin-6; Crohn′s disease